The Relationship between Labor Repair and Labor Absorption in Private Company Employees in Montería, Colombia - Murillo , Hernán Javier Guzmán; Ortega, José Marcelo Torres; Niebles, William (Journal of Ecohumanism, 2024)
The objective of this study is to analyze the relationship between repair capacity and labor absorption in employees of private companies in Montería, Colombia. Organizational repair refers to the ability of employees to adjust and improve their job performance through the identification and correction of errors, while absorption is defined as the state of deep immersion and concentration in job tasks. Through a simple linear regression model, the study quantifies how repair influences absorption levels in a sample of 250 employees from different private companies in Montería. It was found that employees who implement strategies to correct and improve their performance experience higher levels of absorption, which in turn boosts their motivation and productivity. The results suggest that organizational repair acts as a resource that improves work engagement, favoring concentration, fluidity in performance and the general well-being of employees. This study provides empirical evidence on the importance of reparation strategies in the work context and their direct relationship with organizational vigor and performance.